Reconceptualising the Post-peasantry: Household Strategies in Mexican Ejidos - Schüren, Ute (European Review of Latin American and Caribbean Studies, 2003)
In his widely discussed book Micheal Kearney  (1996) questions the peasant concept in anthropology. Current global conditions, he argues, do  not favour the perpetuation of the peasantry.  Therefore, this category should be abandoned. Instead, Kearney proposes to call the globalised  postpeasant individuals polybians. Because they  carry out different economic strategies they are  slippery creatures, defy social bounds, and have  multiple social identities. Kearney is right in criticising the essentialism of earlier approaches.  However, his concept runs the risk of establishing  a new essentialisation. I will argue against the  point forwarded by Kearney and many others that  recent trends in globalisation have resulted in radical new household strategies of rural people.  Historical and ethnographical data of rural communities (ejidos) the Chenes region on the central  Yucatan peninsula, Mexico illustrate that the rural  economy has changed constantly – sometimes  slowly, sometimes radically – including processes of occupational multiplicity, wage labour and  migration. People adopted new or revived former  economic strategies in response to changing local,  regional, national and global processes. There was  no unilinear sequence from peasant to migrant.  During the ‘golden years’ of chicle exploitation in the 1930s and the early 1940s, for example, many  peasants became wage labourers in the chewing  gum industry. Later, a peasantisation process  developed due to the bust of the chicle economy  and increasing prices of corn.  Resumen: Reconceptualizar lo post-campesino: estrategias domésticas en los ejidos  mexicanosEn su libro ampliamente discutido, Micheal  Kearney (1996) cuestiona el concepto ‘campesino’ en la antropología. Las condiciones  globales de hoy en día, argumenta Kearney, dificultan la perpetuación de ‘lo campesino’. Por lo  tanto, esta categoría debe entrar en desuso. En su  lugar, Kearney propone llamar polybians a los  post-campesinos globalizados. Ya que ellos son  criaturas inaprensibles al desarrollar diferentes  estrategias económicas, desafían límites sociales  y tienen múltiples identidades sociales. Kearney  está en lo cierto al criticar el esencialismo presente en perspectivas anteriores. Sin embargo, su  concepto corre el riesgo de convertirse a su vez  en un esencialismo. Yo discuto sobre la perspectiva que Kearny y otros autores proponen al decir  que el rumbo reciente de la globalización ha  producido estrategias domésticas radicalmente  nuevas entre la gente rural. Datos históricos y  etnográficos de las comunidades rurales (ejidos)  de la región chen en el centro de la península de  Yucatán, México, ponen de manifiesto que la  economía rural ha estado en constante cambio – algunas veces lentamente, otras más intensamente-, visible a través de procesos de ocupación múltiple, trabajo asalariado y migración.  La gente ha revitalizado o creado estrategias económicas en respuesta a cambiantes procesos  locales, regionales, nacionales y globales. No ha  habido una trayectoria lineal en la transición de  campesino a migrante. Por ejemplo, durante la  llamada ‘época dorada’ de la extracción de chicle  de 1930 hasta comienzo de la década de 1940,  muchos campesinos se convirtieron en trabajadores asalariados en la industria de la goma de mascar.  Tiempo después, los trabajadores se volvieron  campesinos, debido a la quiebra de la economía del  chicle y el incremento en los precios del maíz.